PUPIL'S SELF-CONCEPT AND ASSESSMENT IN INQUIRY-BASED TECHICAL EDUCATION - ČÁSTKOVÁ, Pavlína; KROPÁČ, Jiří (Trends in education, 2015)
The paper responds to current educational trends in polytechnic education and presents inquirybased education as the one of the opportunities for the development and the pupil´s self-evaluation. On the basis of this contribution is an attempt to present the context of self-concept in relation to technical education. At the same time it presents the student self-assessment as an integral part of their self-image.
Keywords: pupil´s self-concept; pupil´s self-assessment; technical education; inquiry-based education.